Kedudukan dan Kekuatan Hukum Surat Edaran Mahkamah Agung (Sema) Dalam Hukum Positif Indonesia - Andhika Santoso, Raihan; Elan Jaelani; Utang Rosidin (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
The legal products of the Supreme Court are not the same as laws. If the law does not understand or regulate something, the Supreme Court can issue policy regulations based on its authority. However, such a thing is not always done. For example, in 1963 the Supreme Court issued Circular Letter Number 3, which effectively canceled a number of Articles in the BW because it was considered unfair. . Researchers use normative research methods to obtain relevant material and explanations for the formulation of the problem as well as to obtain research-based understanding and explanations raised. Normative research is a type of research conducted through a review of literature (secondary sources). The type of normative research chosen is normative juridical, because the starting point of this research is to use legal norms or existing laws and regulations to analyze the problem under study. The results show that the Position and Strength of the Supreme Court Circular Letter (SEMA) in the legal system in Indonesia is recognized outside the hierarchy of laws and regulations and has binding legal force in accordance with the words of Article 8 Paragraph (1) and (2) of Law no. 12 of 2011